PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI KEBERAGAMAN SOSIAL DAN BUDAYA KELAS IV SD - Clarista Cahyanisam; Sri Utaminingsih; Nur Fajrie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher-centered learning results in low critical thinking skills of elementary school students. Initial observations in grade IV of SD Negeri Sukolilo 02 showed low student activity and minimal involvement in higher-order thinking processes in Pancasila Education learning on social and cultural diversity. To overcome these problems, the Discovery Learning learning model was implemented. This study aims to determine the effect of implementing the Discovery Learning model on the critical thinking skills of grade IV students of SD Negeri Sukolilo 02. This study used a quantitative approach with an experimental method and a one-group pretest-posttest design. The subjects were grade IV students of SD Negeri Sukolilo 02. Data collection techniques included tests, observations, and documentation with instruments in the form of critical thinking ability test questions. Data analysis was carried out using the SPSS program through a paired sample t-test. The results showed an increase in students' critical thinking skills after the implementation of the Discovery Learning model. The average pretest score of 45.60 increased to 80.80 in the posttest. The results of the hypothesis test show a significance value (2-tailed) of 0.000 < 0.05, so Ha is accepted and H0 is rejected. Thus, the application of the Discovery Learning model has a significant effect on students' critical thinking skills in Pancasila Education learning for grade IV of SD Negeri Sukolilo 02.